Possibility of Maintaining Health in Russia Using Traditional Chinese Medicine: a Review - R.Ya, Tatarintseva; I.E, Pisarevskiy; A.V, Ageeva; E.Y, Lebedeva; G.G, Apriamashvili; M.Yu., Kadoshnikova (Pharmacognosy Communications)
In recent years patients as well as physicians in our country have been interested in Traditional Chinese Medicine, which has 5 thousand year history. The principles of Traditional Chinese Medicine are based on disease prevention. For successful prevention of diseases and supporting good level of health it is necessary to know the laws of dialectics in nature and adapt this knowledge to humans, and to maintain the balance between a human and the environment with the help of these laws. Chinese doctors say that treating a disease is the same as to start digging a water well when you are thirsty. Since ancient times in Traditional Chinese Medicine medicinal and food plants have successfully been applied for prevention and treatment of diseases, also acupuncture, moxibustion and massage have successfully been used. We believe that using knowledge and apply- ing Traditional Chinese Medicine in their medical practice doctors of various clinical specialties expand the opportunities of rehabilitation measures and keeping health of the population in the Russian Federation.
Keywords: Chinese Medicine; Disease prevention; Health of population; Herbal; Yang; Yin.